A New Framework of IND-CCA Secure Public Key Encryption with Keyword Search. (10th June 2020) - Ma, Sha; Huang, Qiong
Abstract: In the era of cloud computing, public key encryption with keyword search (PEKS) is an extremely useful cryptographic tool for searching on encryption data, whose strongest security notion is indistinguishability encryption against chosen ciphertext attack (ind-cca ). Adballa et al. presented a transformation from identity based encryption (IBE) to PEKS in the Theory of Cryptography Conference 2010. This paper proposes a new framework of ind-cca secure PEKS in the standard model. Our main technical tool is a newly introduced notion of smooth projective hash function with key mapping, in which the hash key hk is mapped into another mapping projection key mhp besides the classical projection key hp . Finally, we provide an instantiation of our framework based on symmetric eXternal Diffie–Hellman assumption.